2012
DOI: 10.11160/bah.12003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring body temperatures in small lacertids: Infrared vs. contact thermometers

Abstract: Infrared thermometers (IRT) are gaining popularity in herpetological thermal ecology due to their several advantages compared to contact thermometers (CT). To evaluate their accuracy in small lacertids, lab parallel measurements using IRT and CT are compared for a set of 52 adult lizards belonging to four different Podarcis forms, including males, pregnant and non-pregnant females, exposed to a photothermal gradient. Skin temperature was measured with an IRT and cloacal temperature with a CT at 10 time interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…The T p value of T. mauritanica (mean, 29.807C) is substantially lower than that of the diurnal gecko Ptyodactylus hasselquistii puiseuxi from Israel (33.57C; Arad et al 1989) or averaged diurnal lizards from Australia (35.07C), the Kalahari (36.47C), and North America (37.17C; . As also documented in Gil et al (1994), our results do not support a negative relationship between mean T p and size or mass, as reported by Carretero (2008) or even by Vasconcelos et al (2012) using the Cape Verdean Tarentola substituta. In fact, our results, supported by robust sample sizes, suggest that there is no correspondence between T p and body size.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The T p value of T. mauritanica (mean, 29.807C) is substantially lower than that of the diurnal gecko Ptyodactylus hasselquistii puiseuxi from Israel (33.57C; Arad et al 1989) or averaged diurnal lizards from Australia (35.07C), the Kalahari (36.47C), and North America (37.17C; . As also documented in Gil et al (1994), our results do not support a negative relationship between mean T p and size or mass, as reported by Carretero (2008) or even by Vasconcelos et al (2012) using the Cape Verdean Tarentola substituta. In fact, our results, supported by robust sample sizes, suggest that there is no correspondence between T p and body size.…”
Section: Discussionsupporting
confidence: 65%
“…Earlier studies of preferred T p of the Moorish gecko (Gil et al 1994;Arad et al 1997;Carretero 2008) have indicated very distinct results with respect to temperature patterns and mean T p , which might be related to the collection of data during distinct experimental seasons and the use of different evolutionary lineages of T. mauritanica. Recently, a study of the niche evolution of this group has been performed that correlates presence records of all lineages and current bioclimatic variables to build species distribution models (SDMs; Rato et al 2015).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…With increasing distance the measurement 'spot' becomes too large for measuring the temperature of specific regions. Nevertheless, these devices gave equally good measurements of skin temperature in ectotherms as did thermistors placed on the skin [100], but of course peripheral temperature recorded with this technique will differ from cloacal temperature [101]. Infrared sensors can provide continuous monitoring of surface body temperature with an automated data collection system or can also be used remotely in nest boxes to study thermoregulation and torpor [102].…”
Section: Alternatives To Infrared Thermography For Remote Non-contacmentioning
confidence: 99%
“…Skin surface temperature (T sk ) gives an accurate estimate of cloacal temperature (T b ) in small lizards (Herczeg et al, 2006;Hare, Whitworth & Cree, 2007;Carretero, 2012). This non-invasive technique minimizes disturbance to animals and avoids handling stress.…”
Section: Validation Of Body Temperature Measurementsmentioning
confidence: 99%